2021
DOI: 10.1021/acsomega.1c02088
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of α-Ga2O3 by Water Oxidation of Metallic Gallium as a Photocatalyst for CO2 Reduction with Water

Abstract: We have succeeded to synthesize gallium oxide consisting of α-phase (α-Ga2O3) with the calcination of GaOOH obtained by a direct reaction of liquid Ga metal with water for the first time and found that α-Ga2O3 exhibits photocatalytic activity for CO2 reduction with water and water splitting as well. The calcination above 623 K converted GaOOH to α-Ga2O3, and the samples calcined at 723–823 K were well crystallized to α-Ga2O3 and promoted photocatalytic CO2 reduction with water, producing CO, H2, and O2. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
3
1
Order By: Relevance
“…It should be noted that the selectivity of CO production is nearly 40% which is quite high for the photocatalytic CO 2 reduction without the Ag cocatalyst. Furthermore, the CO production rate is much higher than those observed in the previous study 11 in which α-Ga 2 O 3 was synthesized under higher temperature and longer calcination time was employed and hence the nano-pores might have been disappeared. Considering the small mass of the sample used as the photocatalyst (0.05 g) and non-use of a co-catalyst, it can be concluded that the synthesized meso-porous α-Ga 2 O 3 showed quite high activity for photocatalytic reduction of CO 2 .…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…It should be noted that the selectivity of CO production is nearly 40% which is quite high for the photocatalytic CO 2 reduction without the Ag cocatalyst. Furthermore, the CO production rate is much higher than those observed in the previous study 11 in which α-Ga 2 O 3 was synthesized under higher temperature and longer calcination time was employed and hence the nano-pores might have been disappeared. Considering the small mass of the sample used as the photocatalyst (0.05 g) and non-use of a co-catalyst, it can be concluded that the synthesized meso-porous α-Ga 2 O 3 showed quite high activity for photocatalytic reduction of CO 2 .…”
Section: Resultscontrasting
confidence: 57%
“…In a previous work, Sonoda et al 11 have reported first time that α-Ga 2 O 3 formed by the calcination of GaOOH made of liquid metal Ga hydroxidation with water showed high photocatalytic activity for the CO 2 reduction with water. Following the previous work, in this work, we have succeeded to synthesize meso-porous α-Ga 2 O 3 which shows significantly high photocatalytic activity for CO 2 reduction with water under UV light illumination, using liquid Ga metal as a starting material, through the hydroxidation to GaOOH and Ga(OH) 3 followed by the calcination of these hydroxides.…”
Section: Introductionmentioning
confidence: 99%
“…[31] For example, Cu 2 O crystals with different exposed crystal facets exhibit different bandgaps owing to the ultrathin surface layers (~1.5 nm) on the crystal facets, which have different band-bending degrees and structures, resulting in dissimilar band energies. [32] Therefore, the bandgaps and band edges of Cu 2 O with various morphologies, such as spheres, cubes, rhombic dodecahedra, and octahedra, differ because of the different ratios of the (100), (111), and (110) crystal facets. [32][33] In addition, the electronic structure of every crystal facet is distinctive, which directly affects the interactions between the catalyst surface and reactants, intermediates, or products.…”
Section: Selfdrivingmentioning
confidence: 99%
“…From this perspective, the selective exposure of specific crystal facets yields extremely different results, which can be used to improve reaction efficiency. For example, Cheng et al [31c] observed that the (111) facet of the designed NH 2 -MIL-125(Ti) MOF was active for the PCRR, and that increasing the proportion of exposed (111) facets could improve photocatalytic performance. Wu et al [11] demonstrated that the (110) facet of the Cu 2 O photocatalyst exhibited activity for the overall PCRR to produce CH 3 OH, whereas the (100) facet was inert (Figure 2d).…”
Section: Selfdrivingmentioning
confidence: 99%